2012
DOI: 10.3201/eid1811.120719
|View full text |Cite
|
Sign up to set email alerts
|

Unchanged Severity of Influenza A(H1N1)pdm09 Infection in Children during First Postpandemic Season

Abstract: Improvement is needed in preventing severe disease and nosocomial transmission in children beyond pandemic situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
2
17
0
3
Order By: Relevance
“…Contradictory findings have been reported in regard to varying disease severity during the pandemic season. Although some researchers did not observe any differences in disease severity between the first and second pandemic outbreaks in 2009 ( 13 , 14 ), another study showed a 4-fold increase in hospitalization and a 5-fold increase in number of deaths in the second wave ( 15 ). However, disease severity of postpandemic seasons has been rarely analyzed.…”
mentioning
confidence: 97%
“…Contradictory findings have been reported in regard to varying disease severity during the pandemic season. Although some researchers did not observe any differences in disease severity between the first and second pandemic outbreaks in 2009 ( 13 , 14 ), another study showed a 4-fold increase in hospitalization and a 5-fold increase in number of deaths in the second wave ( 15 ). However, disease severity of postpandemic seasons has been rarely analyzed.…”
mentioning
confidence: 97%
“…There was no significant effect on pneumonia in children (RR 1.06, 95% CI 0.62 to 1.83; I 2 statistic = 0%). In two zanamivir adult trials, 81,82 pneumonia reporting was based on a stricter definition of X-ray confirmation and there was also no significant treatment effect (RR 1.02, 95% CI 0.35 to 3.02; I 2 statistic = 39%). In nine zanamivir trials, 77,79,80,87,89,91,[97][98][99] pneumonia was a self-reported, investigator-mediated, unverified outcome (see Figures 8 and 9).…”
Section: Pneumoniamentioning
confidence: 99%
“…83,92 were excluded from the meta-analysis because one was only a synopsis 83 and one compared zanamivir to usual care and not placebo. 92 We finally included 26 zanamivir trials: 14 on treatment in adults, [71][72][73]77,[80][81][82]87,89,91,95,[97][98][99] two in children 78,84 and 10 trials in prophylaxis. 70,79,85,86,88,90,93,94,96,100 Our attempt at collecting sufficient information from regulatory files to reconstruct missing CSRs also failed because the information appeared to be insufficient for a reliable reconstruction.…”
Section: Zanamivirmentioning
confidence: 99%
“…Patients admitted to intensive care units were more frequently treated with antivirals: 91% in Canada and 90% in California . In comparison, a nationwide hospital‐based study in Germany showed that only 62% of children <15 years admitted to pediatric intensive care units were treated with oseltamivir both during the pandemic (H1N1) 2009 and the post‐pandemic season 2010/11 …”
Section: Discussionmentioning
confidence: 99%